Exiguobacterium: an overview of a versatile genus with potential in industry and agriculture. (2nd January 2018) - Kasana, Ramesh C.; Pandey, C. B.
Abstract: The bacterial genus Exiguobacterium accommodates many versatile species isolated from diverse environments. Exiguobacterium was described as a genus approximately three decades ago, and now, 17 species, growing over a broad range of temperatures and pH, have been recognized. Various isolates from different niches have been explored for biotechnological and industrial purposes, including enzyme production, bioremediation and degradation of toxic substances released into the environment. Some isolates possess plant growth promoting capabilities, and they are currently being explored for increasing agricultural production. The genome sequences of various strains of this genus have shown the presence of many genes encoding products of importance to agriculture and the environment. In addition, many strains possess stress-responsive genes helping them to colonize and thrive in diverse ecological niches. This review provides a broad view of the versatile genus Exiguobacterium and its potential for applications in agriculture, the environment and industry, as well as the underlying genomic determinants that drive its diversity and adaptability to various extreme environments.